Pepper and salt of classroom group project - Thani, Siti Rohana Mohd; Kuang, Ching Hei (2017)
This research focuses on classroom-based group project works. Specifically, this research aims to identify the key features that are noted in effective classroom group works. In this context, effective classroom group project work implies sessions where intervention strategies (see Cowie & Sharp, 1966) So TL characteristics of attitude, awareness, and appreciation were used effectively to communicate among themselves. These group project interactions were audio recorded in three sessions. For the final group project presentation, groups select their own topics. At the end of the three sessions, all data were compiled for analysis using conversational analysis approach. Following that, a survey was conducted to counter-check students' involvements in the group works. Analysis suggests that many features of effective classroom learning such as attitude, awareness, and appreciation were identified in their group project interactions. The outcome of this research suggests that students learning under normal classroom conditions can be engaged to become more interactive thereby improving their group interaction activities.